1985
DOI: 10.1037/0003-066x.40.5.542
|View full text |Cite
|
Sign up to set email alerts
|

The Day After: The impact of a media event.

Abstract: The Day After is not an ABC movie.., it is a television event•--Robert Ferrante, executive producer, CBS morning news, quoted in Collins, 1983, p. 5 Controversy raged over whether ABC's film, The Day After (TDA;Papazian & Meyer, 1983), was defeatist propaganda or scrupulously apolitical, as well as over whether it was "the most emotionally involving show ever to appear on TV" (Kitman, 1983, p. 21) or "a very close competitor to The Night of the Living Dead for entertainment value" (Grenier, 1983(Grenier,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 10 publications
(10 reference statements)
3
20
0
Order By: Relevance
“…Activists clearly discuss nuclear issues more often with friends and family, although this is much more apparent in the Ridgewood sample than in the Jyvaskyla sample (see Table I). This finding confirms one of the major conclusions of Pavelchak and Schofield [1985] with regard to issue salience: The more often people talk about or think about nuclear war, the more likely they are to be active in its prevention.…”
Section: Discussionsupporting
confidence: 82%
“…Activists clearly discuss nuclear issues more often with friends and family, although this is much more apparent in the Ridgewood sample than in the Jyvaskyla sample (see Table I). This finding confirms one of the major conclusions of Pavelchak and Schofield [1985] with regard to issue salience: The more often people talk about or think about nuclear war, the more likely they are to be active in its prevention.…”
Section: Discussionsupporting
confidence: 82%
“…Findings by other researchers have been mixed on this question. Survey research immediately after the film also found little effect on attitudes (Schofield & Pavelchak, 1985) but this may have been due to the biased nature of the questions. Differences between results reported by broadcasting companies and by psychologists also exist with respect to the issue of the effects of televised violence on children, with the broadcasting companies finding no effects (Rubenstein, 1983).…”
Section: Discussionmentioning
confidence: 94%
“…The Federal Emergency Management Agency, which is responsible for civil defense, received only six calls that evening and the next day. The White House reported only the usual increase in calls from citizens that follows any major political event; legislators reported little increase in war-related mail from constituents (Schofield & Pavelchak, 1985). Nor was there any immediate upswell of public clamor for a nuclear arms freeze.…”
Section: Indifference or Learned Helplessness?mentioning
confidence: 99%